Respiratory Distress in the Newborn with Primary Ciliary Dyskinesia - Evans Machogu; Benjamin Gaston (MDPI AG, 2021)
Primary ciliary dyskinesia (PCD) is inherited in a predominantly autosomal recessive manner with over 45 currently identified causative genes. It is a clinically heterogeneous disorder that results in a chronic wet cough and drainage from the paranasal sinuses, chronic otitis media with hearing impairment as well as male infertility. Approximately 50% of patients have situs inversus totalis. Prior to the development of chronic oto-sino-pulmonary symptoms, neonatal respiratory distress occurs in more than 80% of patients as a result of impaired mucociliary clearance and mucus impaction causing atelectasis and lobar collapse. Diagnosis is often delayed due to overlapping symptoms with other causes of neonatal respiratory distress. A work up for PCD should be initiated in the newborn with compatible clinical features, especially those with respiratory distress, consistent radiographic findings or persistent oxygen requirement and/or organ laterality defects